An implementation of Alan Maley’s proposal on creative writing as a tool for developing writing skills in an EFL tenth graders gropu at Bravo Paez IED School (2016)
This paper aims to determine the impact of the implementation of Alan Maley’s proposal on creative writing as a toolo for developing writing skills in an aEFL tenth graders group at Bravo Paz IED School. This Project describes an Action Reserarch implementation. Instruments for data collection correspond to five workshops developed following somo samples as proposed by the autor afore mentioned. Data analysis follows the steps of advantages, imporvements,and student´s perceptions abour the role of creative writing tasks in language learning as a pedagogical scenario.